Education, literacy, and humanization : exploring the work of Paulo Freire - Roberts, Peter, 1963- (Critical studies in education and culture series., 2000)
A critical introduction to the work of Paulo Friere. The author adopts a holistic approach in exploring the ontological, epistemological, ethical and pedagogical dimensions of Freire's thought, and discusses his approach to adult literacy education.